UPAYA LAUNDRY ATTENDANT DALAM MENANGANI PAKAIAN YANG TERTUKAR DI BEVERLY HOTEL BATAM - Muhammad Mufid Hakim; Nensi Lapotulo (Media Bina Ilmiah, 2022)
Beverly Hotel Batam is a four-star hotel located in the city of Batam, Riau Islands. Mixed and swapped guest clothes is a problem that occurs in the laundry section at Beverly Hotel. This study aims to describe an effort of laundry attendant in dealing with swapped clothes. This study shows the obstacles faced by the laundry section in handling swapped clothes, including the lack of housekeeping responsibility for these clothes which can cause a lot of clothes to be mixed up. For this reason, housekeeping need more thorough and records the clothes that will be going to the laundry immediately to reduce the swapping of clothes. Laundry is a very important part of the hotel because laundry provides a lot of income and laundry also plays a very important role in improving the quality of service at the hotel. The research methodology used in this paper is a qualitative descriptive method, namely by describing the conditions that will be observed in the field more specifically, transparently and in depth. The data collection technique used is in the form of interviews, observation and documentation.